NEXUS Gains Talk 12: Country-Driven Nexus Food and Land Use System Pathways to Achieve Global Goals - Mosnier, Aline; DeClerck, Fabrice A.J. (CGIAR System Organization, 2023)
This webinar focuses on the development of long-term pathways for sustainable food and land use systems. The session delves into the innovative “scenathon” approach implemented by the Food, Agriculture, Biodiversity, Land-Use, and Energy (FABLE) Consortium. During the session, FABLE teams from Colombia, Mexico, and India provide a preview of their ongoing work in constructing pathways through three scenarios: (a) current trends, (b) national commitments, and (c) global sustainability. The teams discuss nexus challenges, emphasizing the interconnections between food, water, biodiversity, land, and healthy diets. Moreover, they demonstrate how the use of the FABLE Calculator can assist in effectively navigating these challenges, while also showcasing how integrated pathways serve as a valuable tool for engaging local stakeholders and informing policies and long-term strategies.